2008
DOI: 10.1007/s11270-008-9632-0
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Lead to Freshwater Invertebrates (Water fleas; Daphnia magna and Cyclop sp) in Fish Ponds in a Tropical Floodplain

Abstract: Acute toxicity of Pb to the water flea; (Daphnia sp) and Copepod, (Cyclop sp) both important component of zooplankton diet of fish was determined by static assay. A positive relationship between percentage mortality and exposure concentration was found in all tests. Mean 24-h LC50, 48-h LC50 and 96-h LC50 values were 2.51±0.0.04 mg l −1 , 1.88± 0.06 mg l −1 and 1.65±0.19 mg l −1 for Daphnia spp and 3.11±0.03 mg l −1 , 2.97±0.05 mg l −1 and 2.61± 0.09 mg l −1 for Cyclop spp, respectively. For all tested species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 28 publications
3
20
0
Order By: Relevance
“…Between the green algae biomass in the Shardara reservoir and zinc, we found a statistically significant positive relat ionship (Krupa et al, 2017), wh ich may be due to the stimulat ing effect of low concentrations of zinc on phytoplankton (Cao et al, 2015). Lethal concentration of lead to cladocerans are two orders of magnitude higher (more than 3.0 mg L -1 ) (Garcı´a-Ga rcı´ et al, 2006), and potentially dangerous concentration -one order of magnitude higher (0.19 mg L -1 ) (Offem & Ayotunde, 2008) than the amount of lead in water of the Shardara reservoir (0.034 mg L -1 ). Quantitative parameters of Copepoda, formed mainly by cyclops Acanthocyclops trajani, were negatively affected by organic polyphosphates, nitrates and total nitrogen.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Between the green algae biomass in the Shardara reservoir and zinc, we found a statistically significant positive relat ionship (Krupa et al, 2017), wh ich may be due to the stimulat ing effect of low concentrations of zinc on phytoplankton (Cao et al, 2015). Lethal concentration of lead to cladocerans are two orders of magnitude higher (more than 3.0 mg L -1 ) (Garcı´a-Ga rcı´ et al, 2006), and potentially dangerous concentration -one order of magnitude higher (0.19 mg L -1 ) (Offem & Ayotunde, 2008) than the amount of lead in water of the Shardara reservoir (0.034 mg L -1 ). Quantitative parameters of Copepoda, formed mainly by cyclops Acanthocyclops trajani, were negatively affected by organic polyphosphates, nitrates and total nitrogen.…”
Section: Discussionmentioning
confidence: 76%
“…With escalation of pollution, Cladocera disappears first from the community (Gagneten & Paggi, 2009). Rotifera and Cyclopoida are more adapted to the conditions of polluted water (Offem & Ayotunde, 2008;Xu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Several possible explanations can account for variations in metal accumulations in tissues. Metabolic rates of organisms, exposure routes, metal mobility values, bioavailability, chelators present in water, and time spent in contaminated water are among important contributing factors (16)(17)(18)(19). In addition, the environmental factors of pH, temperature, salinity, nutrients, organic matter, organic carbon, and Recovery result for spiking (mean value of 5 determinations)…”
Section: Resultsmentioning
confidence: 99%
“…Results have showed that concentrations of lead (Pb) in excess of 0.19 mg·L -1 and 0.30 mg·L -1 can be potentially harmful to Daphnia magna and Cyclop spp. respectively (Offem et al, 2008). Cadmium has long biological life of about 20-30 years.…”
Section: Figurementioning
confidence: 99%